IMPLEMENTATION OF COMMUNITY REPRESENTATIVE SUPERVISORY FUNCTION PERIOD 2014-2019 IN DEVELOPMENT OF MENTAWAI ISLAND DISTRICT - Ikhral Jamar; Darmini Roza; Philips A. Kana (UNES Journal of Swara Justisia, 2020)
DPRD is a regional house of representatives that is domiciled as an element of government administration which has three functions. One of the functions of the DPRD is to supervise the use of the APBD. In the implementation of supervision, there are lacks of effective supervision of the regional assembly by Kabupaten Kepulauan Mentawai that it cause local government budget deficit due to the use of the relevant agencies. This resulted in a lot of development not proceeding as it should be. Based on the results, there are three main points are; first, the implementation of supervision carried out by regional assembly of Kabupaten Kepulauan Mentawai has been running effectively. The supervision of the 2014-2019 regional budget is carried out through three stages, including: the planning stage, the implementation stage, and the evaluation stage. The regional assembly of Kabupaten Kepulauan Mentawai supervises all activities of the regional government apparatus and related parties in implementing the APBD. Second, the concrete obstacles encountered in the implementation of the DPRD's oversight function include: Internal barriers: (a) the background of the suitability of education and tasks is relatively inadequate, (b) Lack of communication between DPRD members and the community, (c) Management and work relationship relationships that are not effective and efficient, (d) The monitoring agenda has not yet been prepared and (e) Lack of standards, systems and procedures for parliamentary supervision (2) External obstacles: (a) Lack of community participation in the implementation of supervision, (b) Government intervention (executive ) is still dominant in the legislative function, and (c) The public is not yet politically aware. Third, efforts made by the government of the Kabupaten Kepulauan Mentawai: Preparing political cadres who are well educated and experienced (2) The system and procedures of the DPRD supervision standards, (3) Making the community information submission container as one of the monitoring tools, (4) Determining the agenda supervision, (5) Establishing related networks / agencies and strategic alliances, (6) Establishing personnel based on competencies and interests.